2018
DOI: 10.1002/marc.201800004
|View full text |Cite
|
Sign up to set email alerts
|

t‐Butyl‐Oxycarbonylated Diamines as Building Blocks for Isocyanate‐Free Polyurethane/Urea Dispersions and Coatings

Abstract: t-Butyl-oxycarbonylated diamines ("di-Boc-carbamates") are investigated as dicarbamate monomers for diamine/dicarbamate polymerizations. Polyureas (PUs) and polyurethanes (PURs) with high molecular weights are prepared from stoichiometric polymerizations of diamines or diols with N-N'-di-t-butyl-oxycarbonyl isophorone diamine (DiBoc-IPDC) using KOt-Bu as a catalyst, while gelation is observed when an excess of DiBoc-IPDC is used with respect to the diamines or diols. Stable dispersions are obtained from PUs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…In 2018, Ma et al published a series of studies exploring nonisocyanate strategies for the production of waterborne polyurea dispersions for coatings. 60,61 Their approach consisted in utilizing a transurethanization-like process in bulk under vacuum. To do so, they copolymerized a bis-alkylcarbamate monomer with two diamines, one of them playing the role of internal dispersing agent (IDA) to form a pre-polymer, that was further dissolved in methanol.…”
Section: Nipus Dispersion By Acetone-like Transesterification Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, Ma et al published a series of studies exploring nonisocyanate strategies for the production of waterborne polyurea dispersions for coatings. 60,61 Their approach consisted in utilizing a transurethanization-like process in bulk under vacuum. To do so, they copolymerized a bis-alkylcarbamate monomer with two diamines, one of them playing the role of internal dispersing agent (IDA) to form a pre-polymer, that was further dissolved in methanol.…”
Section: Nipus Dispersion By Acetone-like Transesterification Processesmentioning
confidence: 99%
“…The authors demonstrated that during the preliminar transurethanization-based step, the nature of the alkyl-leaving group of the bis-carbamate as well as the process conditions (such as high vacuum) were of outmost importance to obtain polyureas of high molar masses. 60,61 The successful implementation of this process thus strongly depends on the ability of the transurethanization reaction to proceed without too many side-reactions. The nucleophilic attack of the diamine onto the bis-carbamate to yield the corresponding urea moiety is in competition with the Nalkylation reaction that can proceed through a decarboxylation mechanism -Scheme 9.…”
Section: Nipus Dispersion By Acetone-like Transesterification Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate hybridization, developing a dispersion of PU or PUr is a critical first step. The development of PUDs and PUr dispersions (PUrD) have gained interest due to the significantly lower volatile organic compound (VOC) content relative to their solvent borne equivalents. In both PUD and PUrD systems, an internal dispersing agent (IDA) is included to impart colloidal stability through neutralized carboxylic acid or cationic functionality.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocarriers are advantageous for improving the solubility of hydrophobic drugs, releasing the payload in a controlled manner, and reducing toxic side effects . Polyurethanes (PUs) are an important family of biocompatible polymers and have been widely applied in biomedical areas, such as drug delivery, tissue engineering, and adhesives, due to their good physical and thermal properties, and good biocompatibility . Recently, PU nanoparticles with stimuli‐responsive properties, including pH, redox, and temperature sensitivity have been widely investigated as drug carriers.…”
mentioning
confidence: 99%